Analysis of grounding performance for different bio filler medium effect - Abd Karim, Ahmad Zahir Zakwan (2019)
The importance of grounding system is when any fault current due to the power system problem, or lightning, can allow that dangerous current passes through the earth. Although with current specification and standardization right now is sufficient, there is no harm to try to improve the performance of the grounding system continually. Thus, the primary purpose of this project is to design and develop a new ground rod prototype with new soil composition. This new soil composition is used bio-material which then will be used as a main material for the grounding medium. The grounding rod will have a two design which is based on the previous research data. There is no any major or significant change on the ground rod except the is of the small electrode at the bottom of this copper rod. The small electrode is designed into the position of horizontal and vertical and then combine with the small ground grid rod which can increase the current dispersion. The performances analysis for the grounding system was based on two main assessments which are the soil resistivity and ground rod resistance. The results show that the vertical ground rod is performing better compared to the horizontal ground rod in term of ground rod resistance. Besides, it shows the depth of the ground rod buried will affect the ground rod resistance significantly. As a conclusion, pineapple leaves filler shows better medium for enhancing the grounding system performance compared with coir filler due to lower lower grounding resistance. Copper sulfate was able to reduce the ground rod resistance value temporarily although for a short duration.